Programming Microsoft Dynamics NAV 2009 - Studebaker, David; Studebaker, David (Packt Publishing, 2009)
This book takes you through the important topics of Microsoft Dynamics NAV with clear explanations and practical example code. There is also a substantial amount of reference material, which has been brought together in one place for you. This book takes care of what the working developer needs to know in order to become productive as quickly as possible. This book is for NAV consultants and developers, and developers or designers of business applications. Managers of NAV development or consultants will also find the book a helpful introduction to understanding NAV development capabilities. Any previous experience with NAV is not expected. Some basic knowledge of object-oriented programming will be quite helpful.